Heart rate variability thresholds: agreement with established approaches and reproducibility in trained females and males - Fleitas-Paniagua, P. R.; Marinari, G.; Rasica, L.; Rogers, B.; Murias, J. M. (Medicine & Science in Sports & Exercise, 2024)
Purpose To determine in trained females and males: i) the agreement between the gas exchange threshold (GET), lactate threshold 1 (LT1) and heart rate variability threshold 1 (HRVT1), as well as between the respiratory compensation point (RCP), lactate threshold 2 (LT2) and heart rate variability threshold 2 (HRVT2) and ii) the reproducibility of HRVT1 and HRVT2 during two-min incremental step protocols.